The Perception of Diversity, Equity, and Inclusion: A Case Study - Baran, Magdalena (Postrzeganie polityk różnorodności, równości i inkluzywności: studium przypadku, 2024)
The topics related to diversity, equity, and inclusion are gaining increasing attention in the modern work environment. In international corporations, employees encounter diversity and multiculturalism daily. That motivates companies to implement norms and policies aimed at creating an inclusive workplace, where all employees, regardless of their identity, cultural differences, sexual orientation, or disabilities, are treated fairly and respectfully within the company community. This research aims to understand employees’ perception of diversity, equity, and inclusion in the Polish branch of an international company. It seeks to explore the initiatives taken by the company to create an inclusive workplace by examining its policies and practices. The research adopts a case study research design and employs surveys and analysis of internal company documents as data collection tools. In the evaluated branch of the company, the results suggest that employees are satisfied with the current level of company actions. However, many employees are unaware or uninformed about the responsibilities and initiatives undertaken by the company.
Baran, M. (2024). The Perception of Diversity, Equity, and Inclusion: A Case Study. W J. Radomska & A. Witek-Crabb (Red.), New Trends in Business Management (s. 64–79). https://doi.org/10.15611/2024.30.7.05
Keywords: diversity; equity; inclusion; equal opportunities; inclusive workplace; różnorodność; równość; inkluzywność; równość szans; inkluzywne miejsce pracy